2021
DOI: 10.1016/j.ajog.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine early in pregnancy and risk of birth defects

Abstract: Background Hydroxychloroquine (HCQ) is generally considered safe in pregnancy for the treatment of rheumatic conditions, but studies have been too small to evaluate teratogenicity. Quantifying the risk of congenital malformations associated with early pregnancy exposure to HCQ is important both in the context of its ongoing use for rheumatological disorders as well as its potential future use for COVID-19 prophylaxis, for which a number of clinical trials are ongoing despite initial trials for COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 35 publications
2
58
1
1
Order By: Relevance
“…Among women with rheumatic diseases, medication use, including HCQ, during pregnancy is recommended to decrease the occurrence of flares, as disease flares have been associated with poorer pregnancy outcomes (Clowse et al, 2006 ; Götestam Skorpen et al, 2016 ; Leroux et al, 2015 ). A recent study by Huybrechts et al ( 2020 ) presented a summary of existing literature surrounding HCQ and the risk of birth defects, noting that these studies have been small case series, small cohort studies of exposed pregnancies, and studies without controls. The authors used two large US claims databases to explore HCQ use and the risk of birth defects among 2,045 HCQ‐exposed and 3,198,589 unexposed pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among women with rheumatic diseases, medication use, including HCQ, during pregnancy is recommended to decrease the occurrence of flares, as disease flares have been associated with poorer pregnancy outcomes (Clowse et al, 2006 ; Götestam Skorpen et al, 2016 ; Leroux et al, 2015 ). A recent study by Huybrechts et al ( 2020 ) presented a summary of existing literature surrounding HCQ and the risk of birth defects, noting that these studies have been small case series, small cohort studies of exposed pregnancies, and studies without controls. The authors used two large US claims databases to explore HCQ use and the risk of birth defects among 2,045 HCQ‐exposed and 3,198,589 unexposed pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…However, concerns about its safety in pregnancy exist given that HCQ crosses the placenta and data on the risks of birth defects associated with HCQ use are sparse (Costedoat‐Chalumeau et al, 2002 ). Though most existing studies have not identified specific signals for safety concerns, a recent cohort study using data from two pharmaceutical claims databases reported an increased risk for any birth defect among women filling prescriptions for HCQ with a daily dose ≥400 mg (Huybrechts et al, 2020 ). While unable to explore the risk of specific birth defects due to the small number of exposed cases, the authors found associations with large groupings of birth defects, including birth defects in the respiratory and urinary tract systems, and oral clefts (Huybrechts et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we are reporting this rare case of bilateral clubfoot in RA's mother. 17 Ventricular septal defects and coarctation of the aorta have been described in babies born to mothers who have received sulfasalazine during pregnancy. However, musculoskeletal abnormalities have not yet been reported as their teratogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Huybrechts et al reports quantified the risk of congenital malformations/birth defects related to early pregnancy administered with hydroxychloroquine and its potential use as prophylaxis were notable [76].…”
Section: Hydroxychloroquinementioning
confidence: 99%